Reflecting on languaging in written narratives to enact personal relations. Issue 4 (16th August 2021) - Beach, Richard; Caraballo, Limarys
Abstract : Purpose: Unlike formalist and functional approaches to literacy and teaching writing, a languaging theory approach centers on the dynamic and interpersonal nature of writing. The purpose of this study was to determine students' ability to engage in explicit reflection about their languaging actions in response to their personal narrative writing to determine those types of actions they were most versus less likely to focus on for enacting relations with others, as well as how they applied their reflections to subsequent interactions with others. Design/methodology/approach: In this qualitative study, thirty seven 12th grade students were asked to write personal narratives and then reflect in writing on their use of languaging actions in their narratives based on specific prompts. Students' explicit reflections about their narratives were coded based on their reference to seven different types of languaging actions for enacting relations with others. Findings: Students were most likely to focus their reflections on making connections, understandings, collaboration and support by and for others as well as expression of emotions, getting feelings out, sharing issues; followed by references to conflicts, arguing, stress, negative perceptions or exclusion; references to ideas or impressions about ethics, respect, values, morals; use of "insider language;" slang, jargon, dialects; use of humor, joking, parody; and references to adult and authorities' perceptions or influences. Research limitations/implications: This research was limited to students' portrayals of their languaging actions through writing as opposed to observations of their lived-world interactions with others. Practical implications: These results suggest the value of having students engage in explicit reflections about their languaging actions portrayed in narratives as contributing to their growth in use of languaging actions for enacting relations with others. Social implications: Students' ability to reflect on their language actions enhances their ability to enact social relations. Originality/value: A languaging perspective provides an alternative approach for analyzing reflections on types of languaging actions.